Q : 4        Simplify.

                (ii) (2x+5)^2-(2x-5)^2​​​

Answers (1)

we use 
a^{2} - b^{2} = (a-b)(a+b)
 In this a = (2x + 5) and b = (2x - 5)
                               (2x + 5)^{2} - (2x - 5)^{2} = ( (2x + 5)- (2x - 5))( (2x + 5)+ (2x - 5))
                                                                               =  ( 2x + 5- 2x + 5)( 2x + 5+ 2x - 5)
                                                                               = (4x)(10)
                                                                                =40x

or

remember that 

(a+b)^2-(a-b)^2=4ab

here a= 2x, b= 5

4ab=4\times 2x \times 5=40x

Preparation Products

Knockout NEET Sept 2020

An exhaustive E-learning program for the complete preparation of NEET..

₹ 15999/- ₹ 6999/-
Buy Now
Rank Booster NEET 2020

This course will help student to be better prepared and study in the right direction for NEET..

₹ 9999/- ₹ 4999/-
Buy Now
Knockout JEE Main Sept 2020

An exhaustive E-learning program for the complete preparation of JEE Main..

₹ 12999/- ₹ 6999/-
Buy Now
Test Series NEET Sept 2020

Take chapter-wise, subject-wise and Complete syllabus mock tests and get in depth analysis of your test..

₹ 4999/- ₹ 2999/-
Buy Now
Knockout NEET May 2021

An exhaustive E-learning program for the complete preparation of NEET..

₹ 22999/- ₹ 11999/-
Buy Now
Exams
Articles
Questions